1996
DOI: 10.1007/bf00327907
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of riparian species and stream detritus using multiple stable isotopes

Abstract: Multiple stable isotopes were used to determine the effectiveness of distinguishing among several dominant riparian species and aquatic macrophytes both spatially (three sites) and temporally (three seasons) along an 8-km reach of a blackwater stream. The differences in isotopic composition were used to assess contributions of various organic matter sources to the detrital pool of the stream. Samples of riparian and aquatic macrophyte vegetation and detritus were collected at three times to represent early lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…Amount and composition of detritus was sitespecific, both influenced by the littoral slope and reflecting the relative abundances of plant sources. The stable isotope ratios of the allochthonous species fell within the range of C 3 plants reported by many authors (Rounick and Winterbourn 1986;Ehleringer 1993;McArthur and Moorhead 1996;France 1995;Talbot 2001;Jones et al 2004;Benstead et al 2006). Submergent species and epilithon had higher d 13 C values than allochthonous plants, similar to those reported by Benstead et al (2006).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Amount and composition of detritus was sitespecific, both influenced by the littoral slope and reflecting the relative abundances of plant sources. The stable isotope ratios of the allochthonous species fell within the range of C 3 plants reported by many authors (Rounick and Winterbourn 1986;Ehleringer 1993;McArthur and Moorhead 1996;France 1995;Talbot 2001;Jones et al 2004;Benstead et al 2006). Submergent species and epilithon had higher d 13 C values than allochthonous plants, similar to those reported by Benstead et al (2006).…”
Section: Discussionsupporting
confidence: 78%
“…Stable isotope analysis (SIA) often allows the unequivocal identification of elemental sources of organic deposits (McArthur and Moorhead 1996), and thus the contribution to higher trophic levels (Boon and Bunn 1994;Loneragan et al 1997;McCutchan and Lewis 2002;Peterson and Fry 1987;Phillips and Gregg 2003;Benstead et al 2006). However, the presence of multiple organic sources hamper SIA because mathematical Mixing Models used to estimate the contribution of each source to the mixture are constrained by the number of isotopes that can be analysed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the floodplain (Hamilton and Lewis, 1992) and riparian (McArthur and Moorhead, 1996) regions. However, the utility of SIA for identifying sources can be limiting for several…”
Section: J7mentioning
confidence: 99%
“…This has led to the development of mixing models that enable more accurate determination of sources, but the relative contribution of each source must be known. Others have suggested that analysing multiple stable isotopes simultaneously McArthur and Moorhead, 1996), or combining other tracers such as C/N ratios (Andrews et al, 1998), could prove to mitigate this problem.…”
Section: Reasonsmentioning
confidence: 99%